‘The child that I left behind’: memory, trauma, and the reconstruction of childhood in Nakba narratives - Nasser, Rawan (Frontiers in Psychology, 2025)
IntroductionThis article analyzes Palestinian refugee childhood memories, focusing on how displacement and survival intersect within the context of ongoing settler-colonial violence. Challenging conventional Western trauma frameworks that view trauma as discrete, time-bounded events amenable to therapeutic resolution, this research conceptualizes Palestinian children’s experiences as sociogenic trauma emerging from colonial structures rather than individual pathology.MethodsDrawing on 34 interviews with Palestinian refugees from Lydda who experienced the 1948 Nakba as children or were born shortly after, the study uses the child as method framework to analyze childhood memories as complex and dynamic sites where trauma and adaptive survival mechanisms coexist and shape individual and collective experiences.ResultsFindings reveal systematic processes of “unchilding”—the deliberate eviction of Palestinian children from childhood through invisibilization, dehumanization, and forced premature maturation—alongside survival strategies such as selective sensory silencing and strategic memory suppression. The study demonstrates how Palestinian refugees mobilize childhood memories to position themselves within ongoing displacement, deploying childhood as a cultural-political category to navigate present conditions of ongoing Nakba and resistance.DiscussionThis study contributes to scholarship that centers Palestinian perspectives by illuminating how childhood memories function as sites of resistance that protect Palestinian knowledge from appropriation. It calls for fundamental changes in academic and professional practice, advocating approaches that honor Palestinian epistemologies while challenging Western frameworks’ claims to universality in understanding trauma and survival.